2021
DOI: 10.3390/en14020358
|View full text |Cite
|
Sign up to set email alerts
|

Loading Performance of a Novel Shearer Drum Applied to Thin Coal Seams

Abstract: The poor loading performance of shearer drums restricts the development and production efficiency of coal in thin coal seams. Changing operation and structural parameters can improve the drum’s loading performance to some extent, but the effect is not obvious. A two-segment differential rotational speed drum (TDRSD) was proposed after analyzing the drum’s influence mechanism on coal particles. To further reveal the drum’s coal loading principle, the velocity, particles distribution, and loading rate were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To this end, they proposed a novel segmented differential drum in which the lower speed of the front drum reduces the tangential ejection speed of coal particles to lower the probability of being thrown into the goaf, and the higher speed of the rear drum helps to improve the loading speed of coal particles at the coal discharge port of the drum. The results obtained by Gao et al 23 show that the novel drum can improve the loading performance significantly, thus providing guidance on drum design. By utilizing the DEM to study the accumulation and movement of particles under the action of drum vanes, an axially inclined helical vane drum was designed by Sun et al 24 , which could effectively improve the coal loading rate.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To this end, they proposed a novel segmented differential drum in which the lower speed of the front drum reduces the tangential ejection speed of coal particles to lower the probability of being thrown into the goaf, and the higher speed of the rear drum helps to improve the loading speed of coal particles at the coal discharge port of the drum. The results obtained by Gao et al 23 show that the novel drum can improve the loading performance significantly, thus providing guidance on drum design. By utilizing the DEM to study the accumulation and movement of particles under the action of drum vanes, an axially inclined helical vane drum was designed by Sun et al 24 , which could effectively improve the coal loading rate.…”
Section: Introductionmentioning
confidence: 95%
“…Based on this, Gao et al 22 developed a drum with a variable cross-section hub to improve the coal loading performance of the drum and studied the motion behavior of particles and the filling rate of the envelope zone to further identify the influence mechanism of the hub on the coal loading, thus obtaining the optimal shape and parameters. Moreover, by dividing the coal wall into different areas according to different cutting depths in the simulation, Gao et al 23 found that the broken coal particles at the larger cutting depth, more specifically, at the endplate position, are difficult to be conveyed to the scraper due to the long distance, resulting in the prevalence of scattered coal in the channel and the emergence of floating coal. To this end, they proposed a novel segmented differential drum in which the lower speed of the front drum reduces the tangential ejection speed of coal particles to lower the probability of being thrown into the goaf, and the higher speed of the rear drum helps to improve the loading speed of coal particles at the coal discharge port of the drum.…”
Section: Introductionmentioning
confidence: 99%
“…The pick spatial position and attitude are the main factors affecting pick consumption and rock cutting performance for the cutting head [ 9 13 ]. When the characteristic size of the cutting head is confirmed, the pick spatial position can be determined by the two parameters of the helix shape and the cutting line spacing [ 14 16 ]. In the conventional design process, the helix geometry is determined first, and then the picks are arranged on the helix with appropriate spacing according to rock properties.…”
Section: Introductionmentioning
confidence: 99%